Polish Authoritarian Turn of "Law and Justice": Essential and Ideological Foundations and Consequences - T. E. Mirzadzhanov (Сравнительная политика)
The article examines the foundational principles of the Law and Justice (Prawo i Sprawiedliwość, PiS) party, focusing on its authoritarian-populist stance, ideological roots, and policy objectives. It delves into the repercussions of PiS's anti-democratic measures, particularly in the arear of the Constitutional Court, human rights, and protection of human rights, and control over media outlets and news agencies. These actions have led to visible and anticipated outcomes, sparking widespread criticism both domestically, from Polish opposition groups and activists, and internationally, from foreign politicians and organizations. The article aims to provide a thorough description and examination of the ongoing political dynamics within the country, specifically the authoritarian trends stemming from PiS's nationalist-imbued populism being elevated to the status of the state's governing ideology. The study segments the political landscape into three distinct categories: the underlying factors driving PiS's authoritarian trajectory rooted in its overarching authoritarian-populist worldview, the attitudes, imperatives, and strategies shaping PiS's policy responses and problem-solving approaches, and the political shifts observed as a consequence of these dynamics.